Unicuspid Aortic Valve in Patients Undergoing the Ross Procedure - Gofus, Jan; Fila, Petr; Vobornik, Martin; Ondrasek, Jiri; Nemec, Petr; Sterba, Jan; Cermakova, Eva; Tuna, Martin; Vojacek, Jan (The Annals of thoracic surgery, 2023)
BACKGROUND: The prevalence and outcomes of the unicuspid aortic valve (UAV) in patients undergoing the Ross procedure have been strongly underreported in the current literature. We sought to evaluate this in comparison with bicuspid (BAV) and tricuspid valve (TAV) in our Ross cohort. METHODS: This was a retrospective observational study of patients undergoing the Ross procedure at 2 dedicated centers between 2009 and 2020. Primary end points were the risks of midterm autograft reoperation and the onset of at least moderate aortic regurgitation during follow-up. The secondary end point was to compare the perioperative outcomes between the groups. RESULTS: Included in the analysis were 286 patients, of those 39% with UAV, 52% with BAV, and 9% with TAV. UAV patients were operated on at the youngest age (P < .001) and more often for a combined hemodynamic aortic valve pathology (P = .02). They had the largest aortic root dimensions: annulus (P = .01), Valsalva sinuses (P = .11), sinotubular junction (P = .001), and ascending aorta (P < .0001). The risks of reoperation (P = .86) and the onset of aortic regurgitation (P = .75) were comparable among the groups over the follow-up of 4.1 years. There was no difference in perioperative outcomes. CONCLUSIONS: UAV is a separate unit characterized by a distinct hemodynamic pathology and generated aortopathy. It is not associated with a higher risk of reoperation or new onset of aortic regurgitation after the Ross procedure in the midterm postoperatively. At the current state, UAV remains acceptable for the Ross procedure.
Keywords: Retrospective Studies; aorta; Aorta; aortální insuficience; Aortic Valve Insufficiency; retrospektivní studie; Humans; nemoci srdečních chlopní; Aortic Valve; aortální chlopeň; Heart Valve Diseases; lidé